2024
DOI: 10.3390/bs14010052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Impulsivity and Interpersonal Problems on Adolescent Depression: A Cross-Lagged Study

Yanan Yang,
Mingyangjia Tian,
Yu Liu
et al.

Abstract: The dynamic changes over time in the relationships between impulsivity, interpersonal problems, and depression warrant further exploration. This study delves into the roles of impulsivity and interpersonal issues in the progression of adolescent depression over a year, using a sample of 271 Chinese adolescents (51.7% male, Mage = 12.60 ± 0.69). At three time points, impulsivity levels were assessed with the Chinese version of the Barratt Impulsiveness Scale-11, interpersonal problems with the Adolescent Self-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Impaired interpersonal relationships are a typical manifestation of an unmet need for belonging, and depression is one of the main consequences of interpersonal trauma [20]. A cross-lagged study found that relationship problems predispose adolescents to maladjustment, as evidenced by elevated levels of depression six months later [21].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired interpersonal relationships are a typical manifestation of an unmet need for belonging, and depression is one of the main consequences of interpersonal trauma [20]. A cross-lagged study found that relationship problems predispose adolescents to maladjustment, as evidenced by elevated levels of depression six months later [21].…”
Section: Introductionmentioning
confidence: 99%